Reducing skin tears, workload, and costs in the frail aged: replacing showers with bath cloths - Sharp, Catherine; Campbell, Julie (Asian Journal of Medical Sciences, 2022)
Background: Two Nurse Consultants, as part of their usual practice of auditing wounds in a 25-bed dementia unit of an aged care facility in Sydney, Australia, reported on skin tears (STs), wounds that occur mainly on the forearms of the elderly and often during showering. Aims and Objectives: The main aims were to measure and reduce the prevalence of STs; replace showers with HiCare™ bath cloths; reduce the nurses’ workload; reduce costs for laundry and wound dressings and a new regime for showering residents introduced. Materials and Methods: Bedside training was given to care staff, and data on time taken to bed-bath, HiCare™ bath and shower, were collected, collated and costs estimated. Results: Three of 25 residents (12%) had a total of six STs. Following the introduction of the HiCare™ bath system the incidence of STs decreased by 96% in 6 weeks and cost savings were AUD 6.76/resident. Conclusion: The number of showers performed each day by nurses was reduced allowing nurses more time to feed residents, go for a walk and sit in the garden. These practice changes benefit the residents as well as the nurses.